The labyrinth technique in Aethiopica of Heliodorus - de Souza Graebin, Geruza (Revista Archai, 2023)
Heliodorus is known for his elaborate narrative technique. This effect is due to ekphrasis, a resource widely used by sophists and recommended in textbooks of rhetoric (Progymnasmata). In the first block of the work, Heliodorus uses this resource, but not randomly. There is an image, literally or metaphorically repeating itself: the labyrinth. Our intention is to demonstrate that the repetitions have a commonality, in addition to a strong hermeneutical appeal. Moreover, the labyrinths are introduced in the part where the narrative is skillfully written in medias res. It is precisely in this passage that the reader, as in a labyrinth, is meanderingly led by several paths, until he reaches the understanding of the opening scene, at the mouth of the Nile. The analysis of the procedures used by Heliodorus leads to the conclusion that the succession of textual or imagethic labyrinths places the reader in a game, from which he can only emerge at the end of the fifth book.